COMMUNICATIVE LANGUAGE TEACHING WITH REALIA TO ENHANCE STUDENTS’ ENGLISH VOCABULARY - Resky Indrayana Uda Patmi; Sabaruddin Sabaruddin (LP2M Institut Agama Islam Muhammadiyah Sinjai, 2021)
This research discusses vocabulary improvement of second year student at Madrasah Tsanawiyah Madani Pao-pao, South Sulawesi, Indonesia using Communicative Language Teaching with Realia. Researchers intend to answer the question